Microencapsulation of Cosmos caudatus Kunth Extract using Sodium Alginate and In Vitro Antioxidant Activity Test - Fadlila, Safina Samara Nur; Puspita, Oktavia Eka; Ningsih, Zubaidah; Safitri, Anna (UI Scholars Hub, 2024)
This study aims to encapsulate Cosmos caudatus K. leaf extract in sodium alginate crosslinked with calcium chloride (CaCl2) as coating materials through freeze-drying. Antioxidant assays were performed to evaluate the applicability of the microcapsules as antidiabetic medicines. Their characteristics, antioxidant activity, and encapsulation efficiency (EE) were also examined. Results indicated that the concentration of sodium alginate and pH influenced the manufacturing process of the microcapsules. The highest EE was obtained at pH 6 and alginate concentration of 2% (w/v). The IC50 for the antioxidant activity of the microcapsules was 139.96 ± 1.094 μg/mL. Scanning electron microscopy confirmed the presence of irregular and spherical structures on the surface. Fourier transform infrared spectra showed new absorption bands at 1593.10 and 1427.59 cm−1, demexistening the existence of stretching vibrations of COO−. Absorption at 1024.14 cm−1 demonstrated C–C and C–O bond stretching vibrations in the sodium alginate–CaCl2 crosslinks. Fourier transform infrared spectrum analyses indicated that sodium alginate and CaCl2 formed chemical bonds, enabling microencapsulation. This study discovered that microencapsulation is a highly prospective and adaptable strategy for enhancing the medicinal use of plant extract.